Psychosocial assessment of lung cancer patients and their caregivers - Clara, Cátia Andreia (2021)
Lung cancer (LC) is one of the most common types of cancer disease worldwide. Studies in the field show that the appearance of a pathology of this form causes changes not only in the patient’s life, namely psychological problems, functional limitations and poorer health due to the clinical consequences of treatments, but also in their family, where caregivers often face the challenge of providing long-term daily care that induces a physical, psychosocial and financial burden (Borges et al., 2017; Hewitt et al., 2003; Tan et al., 2018). The main objective of the present study is to compare and relate the two groups (patients and caregivers) considering the quality of life (QoL) and symptoms of psychological distress (anxiety and depression). The total sample consisted of 30 patient/caregiver dyads. The instruments used were: Hospital Anxiety and Depression Scale; European Organization for Research and Treatment of Quality of Life Questionnaire (EORTC QLQ C-30) and its specific module for lung cancer (LC13); Caregiver Oncology Quality of Life Questionnaire (CarGOQoL) and Zarit Burden Interview Scale (ZBI). The results suggest the influence of depressive symptomatology on patients’ QoL [F(1)=6.390; p<0.05] and depressive and anxious symptomatology and burden on caregivers’ QoL [F(3)=7.815; p<0.001]. A positive association was found between depressive symptomatology of patients and caregivers (r=0.458; p=0.011) and d